Kreativitas anak melalui melukis dengan jari (Finger Painting) di Taman Kanak-Kanak Kota Makassar - Arifin Manggau; Arifuddin Usman (Seminar Nasional LP2M UNM, 2019)
Through the ability of children's creativity which includes fluency, flexibility, authenticity and elaboration. This is because the child really expresses his idea when the activity takes place. Teacher teaching activities show that the teacher teaches finger painting. The purpose of this study was to determine children's creativity through finger painting in kindergarten. The approach chosen in this study is qualitative. The technique of collecting data through observation, interview, and documentation techniques. The results of the study explained that children's creativity through finger painting was first; the factor of Talent in the child, which is a potential that is possessed for the child who comes from within the child, is a provision for him to create the latest works when the activity is truly in harmony with the potential possessed. Second; The role of the environment which includes the family environment and school environment. The family environment is how the role of parents gives stimulation or motivation to their children and understands the extent of their child's potential. While the role of the school environment, namely the interaction of teachers and parents of children to know more about the development of children and the role of schools in preparing adequate facilities and infrastructure in upholding the growth and development of children's potential.